2001
DOI: 10.1152/ajpgi.2001.280.2.g273
|View full text |Cite
|
Sign up to set email alerts
|

Circadian coupling between pancreatic secretion and intestinal motility in humans

Abstract: Human interdigestive intestinal motility follows a circadian rhythm with reduced nocturnal activity, but circadian pancreatic exocrine secretion is unknown. To determine whether circadian changes in interdigestive pancreatic secretion occur and are associated with motor events, pancreatic enzyme outputs, proximal jejunal motility, and plasma pancreatic polypeptide concentrations were measured during consecutive daytime and nighttime periods (12 h each) in seven healthy volunteers using orojejunal multilumen in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 36 publications
4
40
0
1
Order By: Relevance
“…The persistence of circadian rhythms of lipase and a-amylase in food-deprived dogs indicates that they are not driven by the digestive process. This is in agreement with the results of a previous study 2 showing that the daily rhythm of secretion in the pancreas in a rat is independent of gastrointestinal stimulation; these results are in contrast to those of a previous study 16 that showed a direct correlation between amylase output and jejunal motor activity in humans. Thus, circadian effects may modulate interdigestive pancreatic enzyme patterns in dogs.…”
supporting
confidence: 92%
“…The persistence of circadian rhythms of lipase and a-amylase in food-deprived dogs indicates that they are not driven by the digestive process. This is in agreement with the results of a previous study 2 showing that the daily rhythm of secretion in the pancreas in a rat is independent of gastrointestinal stimulation; these results are in contrast to those of a previous study 16 that showed a direct correlation between amylase output and jejunal motor activity in humans. Thus, circadian effects may modulate interdigestive pancreatic enzyme patterns in dogs.…”
supporting
confidence: 92%
“…Additional peak levels of secretion also appear to occur at non-specific time points within the interdigestive (fasting) stages of motility (34,35) . During the fed state, intestinal motor responses to the presence of nutrients in the duodenum appear to occur over the same period of time as pancreatic secretory responses (36) .…”
Section: Secretionmentioning
confidence: 99%
“…A number of studies have documented that MMC and exocrine pancreatic secretion are closely interrelated. Specifically, it has been shown that the secretion of pancreatic enzymes is strictly parallel with the MMC phases, with the highest enzyme secretion observed during phase III of MMC and the minimal enzyme secretion during phase I of MMC [Laerke et al, 2000;Keller et al, 2001]. These findings could indirectly illustrate one of the possible mechanisms to regulate the availability of peptides or amino acids for gut absorption.…”
Section: Discussionmentioning
confidence: 93%